2016
DOI: 10.1002/micr.30103
|View full text |Cite
|
Sign up to set email alerts
|

Vascular territories of the medial upper arm—an anatomic study of the vascular basis for individualized flap design

Abstract: This anatomical study provides valuable data of the medial arm flap in order to be applied clinically. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In addition, the superficial brachial artery, the branches of the biceps artery, the direct cutaneous branches of the brachial artery were also reported as the pedicle artery. 3,8,14 Tinhofer 12 provided clinically data concerning the variable vascular anatomy and demonstrated how to safely design its individual anatomy, matching the varying shapes and sizes of angiosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the superficial brachial artery, the branches of the biceps artery, the direct cutaneous branches of the brachial artery were also reported as the pedicle artery. 3,8,14 Tinhofer 12 provided clinically data concerning the variable vascular anatomy and demonstrated how to safely design its individual anatomy, matching the varying shapes and sizes of angiosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous anatomical studies have demonstrated that the septocutaneous perforators provide the major blood supply of the medial arm flap, 5,6 further studies have clarified the distribution characteristics of these perforators. 6,[17][18][19] The perforator distribution characteristics show that when the medial arm is trisected, constant perforators can be found in each third of the medial arm. 6 Based on these perforators, both proximally and distally based pedicled flap can be designed and elevated for cervicofacial reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of the perforator flap concept over the past several decades, 18,19 we have come to understand that the perfusion of the medial arm tissues is through septocutaneous BAPs; subsequently, the use of the BAP flap in clinical practice has been refined considerably. 7,12,13 A full-length BAP flap could be safely harvested with a single, pulsatile perforator from the brachial artery and robust venae comitantes. 3,7 When combined with tissue expansion, both flap vascularity and size can be greatly augmented, allowing for the reliable transfer of a large area of skin with primary closure of the donor site in a majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several cadaveric and clinical studies have attempted to characterize the perforators of the medial arm using various methodologies. 7,[11][12][13]20,21 Despite their efforts, we have yet to reach a consensus on the anatomical details. As such, we prefer mapping the perforators within the region of the pedicle for each patient, as it can aid in flap design, expedite flap dissection, and avoid unintended injuries to the vascular pedicle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation